Legal Advisory About The Dangers Of Hoax News For Millenial Generations In Man I Probolinggo - Mushafi Mushafi; Faridy Faridy (Veteran Society : Jurnal Pengabdian Masyarakat, 2020)
This community service is packed with legal counseling with the theme "the danger of hoax news for themillennial generation. This is because the millennial generation is a generation that is very vulnerable tobeing affected by hoax news. The millennial generation is the generation that has broad access to socialmedia. Almost every time they will interact with Social Media which contains a lot of hoax information.On this basis, it is important to carry out legal counseling for students of MAN 1 Probilinggo who are partof the millennial generation.